Excavations at Sissi III - Jan Driessen, Charlotte Langohr, Quentin Letesson, Ilse Schoep, Aurore Schmitt, Isabelle Crevecoeur, Sylviane Déderix, Frank Carpentier, Florence Gaignerot-Driesse, Maud Devolder, Simon Jusseret, Florence Liard, Rena Veropoulidou, Christina Tsoraki, Maria (Presses universitaires de Louvain, 2012)
Between 2007 and 2011, the Belgian School at Athens undertook excavations on the Kefali or Buff o hill, east of the village of Sissi, on the north coast of Crete, only a few kilometres east of Malia. The project has revealed the remains of a settlement and cemetery, used during different phases of the Bronze Age (2500-1200 B.C.). This volume details the results of the 2011 campaign, the last in our first 5-year programme. The work in the different zones is described and reports on Late Minoan...